Multimodal enactment of characters in conference presentations. (October 2019) - Valeiras-Jurado, Julia; Ruiz-Madrid, Noelia
In academic oral genres such as conference presentations, speakers resort to more than words to convey meaning. Research also suggests that persuasion, an important element of the communicative purpose of conference presentations, is frequently achieved through a combination of semiotic modes. Therefore, a skilful orchestration of these modes can be considered key to achieving effective communication in this genre. However, our understanding of persuasion has often focused on specific elements of the message considered in isolation and mainly from the linguistic perspective. Relatively little attention has been paid to the overall persuasive effect achieved by the complex multimodal ensemble. This study approaches the analysis of persuasive strategies in conference presentations combining multimodal discourse analysis and ethnographic methods. It focuses on a particular attention-getting technique: enactment of characters, or acting the part of a person that is being referred to. Our analysis shows how it is achieved through the orchestration of different modes such as words, intonation, gestures, head movements, gaze and facial expression.